دراسة تطبيقية لقياس أثر جودة خدمات الوكالات السياحية على الميزة التنافسية مع وجود الابتكار متغيرا وسيطا باستخدام النمذجة بالمعادلات الهيكلية. - وزاني, محمد; زقاي, دياب (جامعة الوادي - University of Eloued, 2016)
The aim of this study is attempting to measure the impact of service quality and innovation to achieve competitive advantage in the insurance sector-in Saida- Algeria, so that the study included a sample of 35 employees, so that the use of statistical analysis using the program (SPSS.V.20), in addition to the program structural modeling using equations (AMOS.V.20) in order to study the various relationships between the proposed variables. The study concluded a number of important results: -The level of insurance services quality does not reach the required level, which clearly reflected on the low level of innovation and thus on competitive advantage . -The results also emphasized the essential role of innovation as a mediator in enhancing the impact of service quality on competitive advantage.
An empirical study to measure the impact of tourism services agencies quality on competitive advantage with the presence of innovation as a mediator variable using structural equation modeling. The case of a group of agencies - Saida – Algeria.
مقال
Keywords: جودة الخدمة السياحية، الابتكار، الميزة التنافسية.